2011
DOI: 10.1089/jwh.2009.1850
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported Versus Measured Height and Weight in Hispanic and Non-Hispanic Menopausal Women

Abstract: Background: Height and weight information is commonly used in clinical trials and in making therapeutic decisions in medical practice. In both settings, the data are often obtained by self-report. If erroneous, this practice could lead to inaccuracies in estimating renal function and medication doses or to inaccurate outcomes of research studies. Previous publications have reported lack of reliability of self-reported weight and height in the general population but have not addressed age-specific and ethnicity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
24
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 26 publications
4
24
0
Order By: Relevance
“…Nonetheless findings from previous studies 15,21,26 of Hispanic/Latinos supported the expectation of under-reporting of weight in this study. In HCHS/SOL the slight mean over-reporting of weight may reflect its size or study design (e.g.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Nonetheless findings from previous studies 15,21,26 of Hispanic/Latinos supported the expectation of under-reporting of weight in this study. In HCHS/SOL the slight mean over-reporting of weight may reflect its size or study design (e.g.…”
Section: Discussionsupporting
confidence: 90%
“…Hispanic/Latinos represented 17% of the adult population in 2013 8 and at least half were born outside of the United States (U.S.). 9 BMI categories, 10–12 age, 5,1114 gender, 5,12 reproductive factors, 15 household income, 12 education, employment and nativity 11 have been described as predictors of weight misreporting in Hispanic/Latinos. Although U.S. Hispanic/Latinos are a diverse ethnic group and may have variable perceptions towards ideal body size 16 , to our knowledge no previous population-based study has described the accuracy of self-reported weight relative to measured weight across more than one Hispanic/Latino background (or heritage).…”
Section: Introductionmentioning
confidence: 99%
“…In Hispanic menopausal women, mean differences of direct minus self-reported measures were 1.5 kg for weight, -2.5 cm for height and 1.4 kg/m2 for BMI. 19 While the errors in self-reported weight we found were similar than those for Hispanic women living in the United States 20 and for Colombian women, 21 errors in self-reported height we found were higher than those reported in the aforementioned studies (0.6 to 1.2 cm). In our study, the possibility that the errors in self-reported anthropometry correspond partially to real changes in weight over time cannot be disregarded.…”
Section: Discussionsupporting
confidence: 62%
“…9 If conscious, the patient could self-report his/her height, but systematic reviews of studies estimating the accuracy of self-reported height found that patients tend to overestimate their true height. 10,11 In the South African setting, patients and/or their family members often have no idea of the patient's height or weight, while language barriers also hamper communication. Estimating patients' height by eyeballing, as many health care professionals do, has also been shown to be very inaccurate.…”
Section: Introductionmentioning
confidence: 99%